Simulation and Experimental Study on Characteristics of Multiorifice Nozzle in Radial Jet Drilling - Tao Zhang; Yumei Li; Hui Lu; Jianing Jiang (Geofluids)
The radial jet drilling (RJD) is a key technology to improve the development efficiency of low-permeability oil and gas resources. In order to seek a reasonable hydraulic engineering parameter combination of hydraulic radial jet drilling, to obtain the optimal hydraulic energy distribution, a jet radial horizontal drilling simulation experiment system of the casing windowing is designed. A sequence of experimental investigations focused on engineering parameters of pump displacement, rotating speed, and frequency of high-pressure plunger pump is performed, and the operability and the feasibility of the experiment are verified. To evaluate the maximum drillable length and the self-propelled force of a jet nozzle, a 3D numerical model based on ANSYS-CFX is developed to evaluate the effects of the inlet flow displacement, the flow rates ratio K, and the angle ratio F:B of the forward orifice and backward orifice of the jet nozzle on its maximum drillable length and self-propelled force by sensitivity analysis. Finally, the comparison of numerical simulation results (Ln), mathematical results (Lm), and experiment results (Le) of the maximum drillable length are presented. It is observed that the simulation results are consistent with the experiment results with an average accuracy of 97.07%. Therefore, the proposed numerical model has a good performance in predicting the maximum drillable length of the multiorifice nozzle. The research results can provide theoretical guidance for improving the rock breaking and drilling capability of radial jet drilling technology.